Inflammatory Markers for Prognosis of COVID-19 Mortality in Hospitalized Indian Patients: A Single-Center Retrospective Study - Nuha Al-Aghbari; Arif Maldar; Mubashir Angolkar; Romana Khurseed; Snehi Shrestha; Pavani Saikam (University of Science and Technology, Sana’a, Yemen, 2023)
Background: Coronavirus disease 2019 (COVID-19) has emerged as a global pandemic associated with poor outcomes and mortality. Therefore, the present study aimed to assess the prognostic value of inflammatory markers in predicting COVID-19 mortality among patients hospitalized at a tertiary care hospital in India. Methods: A retrospective cross-sectional study of 444 hospitalized patients with COVID-19 was conducted in Karnataka state, India from October 2020 to September 2021. Data on inflammatory markers for survivors and non-survivors of COVID-19 were retrieved and analyzed using the receiver operating characteristic (ROC) curve to determine their prognostic value for predicting mortality. Results: Compared to survivors, the median values of all studied serum inflammatory markers were significantly higher in non-survivors of COVID-19. ROC analysis showed that LDH, D-dimer and ferritin were the best predictive markers of COVID-19 mortality. Conclusion: Serum ferritin, LDH, CRP, PCT, IL-6 and D-dimer, are significantly elevated in non-survivors of COVID-19 than in survivors, with all can significantly predict disease mortality. Among these, LDH, D-dimer and ferritin are the best prognostic markers for predicting COVID-19 mortality, with good sensitivity and specificity.